2018
DOI: 10.1038/s41535-018-0105-4
|View full text |Cite
|
Sign up to set email alerts
|

Competing Coulomb and electron–phonon interactions in NbS2

Abstract: The interplay of Coulomb and electron-phonon interactions with thermal and quantum fluctuations facilitates rich phase diagrams in two-dimensional electron systems. Layered transition metal dichalcogenides hosting charge, excitonic, spin and superconducting order form an epitomic material class in this respect. Theoretical studies of materials like NbS 2 have focused on the electron-phonon coupling whereas the Coulomb interaction, particularly strong in the monolayer limit, remained essentially untouched. Here… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 76 publications
1
23
1
Order By: Relevance
“…why NbS 2 is so robust against CDW instability. We note that van Loon et al 36 have already given a detailed account for the competing nature of electron-phonon coupling versus the short-and long-range electron Coulomb interaction, and its prominent role in the absence of CDW instability in NbS 2 .…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…why NbS 2 is so robust against CDW instability. We note that van Loon et al 36 have already given a detailed account for the competing nature of electron-phonon coupling versus the short-and long-range electron Coulomb interaction, and its prominent role in the absence of CDW instability in NbS 2 .…”
Section: Resultsmentioning
confidence: 86%
“…Interestingly, they suggest that the interplay between these parameters strongly enhances both charge and spin susceptibilities in NbS 2 , meaning that it is at the verge of collapsing to a CDW or even a spin density wave phase, if sufficient perturbations are introduced (for example, via local magnetic impurities) 36 . As such, NbS 2 appears to be an ideal candidate for exploring thermal and quantum fluctuations.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we focus on the monolayer metallic TMDs, as these materials are predicted (see Fig. 3) to have large plasmon energies 16,24 and are intrinsically metallic and stable above their charge-density-wave 38 and/or ferromagnetic 39 transition temperature, if any. We find that, in these systems, DFT underestimates the separation between the half-filled d shell bands and the rest of the occupied bands by almost 200 meV and does not yield the correct threshold for single-particle interband excitations.…”
Section: Resultsmentioning
confidence: 99%
“…Given that for any x > 0 this material is metallic, the ability of the functional to predict bandgaps is not relevant in this case. Previous studies have shown that in the x = 1 parent compound NbS 2 , both Coulomb and electronphonon interactions can individually have a strong effect 53 , but their combined effect produces a bandstructure that closely resembles the non-interacting band structure, so we do not consider these interactions explicitly in the current work. A vacuum spacing of 20 A is used to avoid spurious interaction between isolated layers of W 1−x Nb x S 2 .…”
Section: Theoretical Background and Computational Methodsmentioning
confidence: 99%